(untitled) (Eastern Journal of Medical Sciences, 2017)
Background: Cancer is a malignant disease with high incidence in both genders and all age groups. The prevalence of these serious types of cancer which also vary according to age groups and kinds of cancer must be known. Studies are a must to get more attention to these diseases and occasions for prevention of widespread occurrence. Objective: This study was done to study the estimated cancer incidence by gender, age groups, and kinds of cancer in patients. Materials and Methods: 200 cases of cancer patients that were admitted in oncology wards of the hospital after diagnosis with cancer and getting surgery, chemotherapy and radiology in Iran, Zahedan city region, were studied. The study lasted from 12th April 2014 to 20th March 2015. Data collection was during 12 months by follow-up of patients. Collected data of gender, age groups, and kinds of cancer were assessed with frequency statistics test. Results: In particular, females of 35-39 and 50-54 age groups were more vulnerable, and Leukemia was the most frequent type of cancer in the affected population. Cancer research by gender and age groups shows female in 40-44 and male in 35-39 age groups were in high-risk groups. Furthermore, cancer by gender and kinds of cancer indicate that females suffer from leukemia more than males; in contrast, males are affected by lymphoma with higher rate than females. Conclusions: Findings in this study revealed different results in gender, variety of age groups, and kinds of cancer. We studied some important factors to assess high-risk groups in every region of world. This finding gives useful information to reduce high susceptibility risk by positive lifestyle choices, not smoking, eating a healthy diet, being physically active, and improving health education.